INTEGRASI LINIER PROGRAMMING DAN PROGRAM DINAMIK UNTUK MENENTUKAN JUMLAH PRODUKSI KOPI YANG OPTIMUM DI UD. GADING MAS - Novitasari; Mas'ud, M. Imron (Department of Industrial Engineering - Universitas Yudharta Pasuruan, 2020)
The increasingly fierce business competition is currently demanding business players to optimize their products to get the maximum profit, one of which is UD.Gading Mas, which is one of the Small and Medium Industries (IKM) which manages the typical coffee of Pasuruan Regency which has been producing to develop the potential of local resources area. In developing the potential of local resources, the company experienced problems in determining the amount of production, so the company experienced excess products. With the integration of the Linear Program and Dynamic Program approach, it is expected that the company can determine production well, so that neither excess or lack of product. From the results of this study indicate that the planning using a dynamic program is more profitable. With the optimum production level of 1,138 packs with an income of Rp. 22,760,000.